Формирование наноструктурированных пленок иридия и поликластерного алмаза - Belyanin, A. F.; Pal', A. F.; Samoylovich, M. I.; Suetin, N. V.; Dzbanovskiy, N. N.; Mitin, V. S.; Pashchenko, P. V.; Timofeev, M. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
Iridium films and layered “iridium–diamond” structures were formed on Al₂O₃, MgO, and SrTiO₃ substrates. Iridium films were deposited by magnetron sputtering, while polycluster diamond films were obtained using the microwave discharge method. The structure of iridium and diamond films was studied as a function of deposition conditions. The potential applications of polycluster diamond films as heat sinks for hybrid integrated circuits and as control grids in electronic devices are discussed.